Care burden among Iranian family caregivers of patients with schizophrenia: the predictive role of quality of life and life satisfaction - Maede Esmaeeli; Seyedmohammad Mirhosseini; Seyedmohammad Mirhosseini; Somaye Minaei-Moghadam; Saeed Ghasempour; Mohammad Hasan Basirinezhad; Hossein Ebrahimi (Frontiers in Psychiatry)
IntroductionCaring for patients with schizophrenia poses significant challenges for families. This study examined the relationships between caregiving burden, quality of life, and life satisfaction among family caregivers.MethodsThis cross-sectional study was conducted in 2023–24 in Mashhad, Iran. Family caregivers who provided care to a patient with schizophrenia for at least six months completed the Zarit Burden Inventory to evaluate caregiver burden, the 12-item Short Form Health Survey to assess quality of life, and the Satisfaction with Life Scale to measure life satisfaction. The data were analyzed using multiple linear regression.ResultsA total of 211 family caregivers participated, with a mean age of 48.17 ± 14.98 years, of whom 130 (61.61%) were female. Caregiver burden was associated with caregiver-related factors, such as lower life satisfaction (β = -1.27, p < 0.001, 95% CI = -1.48, -1.06), employment status, where housewives experienced lower caregiving burden than unemployed individuals (p = 0.039, β = -4.4, 95% CI = -8.65, -0.21), and marital status, where singles experienced lower caregiving burden than married individuals (p = 0.001, β = -7.89, 95% CI = -11.88, -3.90). In addition, patient-related factors such as longer duration of illness (p < 0.001, β = 0.42, 95% CI = 0.20, 0.64) and lack of health insurance coverage (compared to having coverage) (p = 0.023, β = 5.10, 95% CI = 0.71, 9.49) were associated with higher caregiver burden. Together, these variables explained 62.9% of the variance in the total care burden score.ConclusionThe findings of this study showed that the majority of family caregivers of patients with schizophrenia experienced moderate to severe levels of caregiving burden. This burden was associated with lower levels of life satisfaction, employment status, and marital status of the caregiver, as well as longer duration of illness and lack of health insurance coverage for the patient.